The Relationship Between the Habits of Playing Football With the Achievement Trends of Football Players in Negeri Tulehu, Salahutu Sub-District - Risqy Ahmad Lewenussa; Bahmid Hasbullah; Jonas Solissa (Jurnal Ilmiah Wahana Pendidikan, 2023)
The habit of playing soccer The people of Tulehu country have made playing soccer a habit that is always carried out in their daily activities. Therefore, it is not surprising that Tulehu Country has been given many nicknames that refer to one of the most popular sports in the world, this nickname includes the football village given by Mr. Djohar Arifin who also founded the Football Village monument. The benefits of sports to develop basic concepts in order to improve sports achievement, especially in the sport of football. This research is a quantitative research with a correlational approach. This method is used to find the relationship or relationship of one variable with other variables. Because r_(xy ) or r_h 0.780 at a significant level of 5% is greater than r_(table ), then at a significant level of 5% and 1% the Null Hypothesis (H_O) is rejected, while the alternative hypothesis (H_a) is approved or accepted. The conclusion that the relationship habits have shown real effectiveness, in the sense of the word the habit of playing football is very influential on the tendency to achieve football players in the country of Tulehu, Central Maluku district